2021
DOI: 10.3390/md19020077
|View full text |Cite
|
Sign up to set email alerts
|

Briarenols W–Z: Chlorine-Containing Polyoxygenated Briaranes from Octocoral Briareum stechei (Kükenthal, 1908)

Abstract: Briareum stechei is proven to be a rich source of 3,8-cyclized cembranoids (briarane) with a bicyclo[8.4.0] carbon core. In the present study, four previously unreported briaranes, briarenols W–Z (1–4), along with solenolide A (5), briarenolide M (6), briaexcavatolide F (7), and brianolide (8), were isolated and characterized through spectroscopic analysis, and the absolute configuration of 8 was corroborated by a single-crystal x-ray diffraction analysis. Briaranes 2 and 5 were found to induce significant inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…576 In addition, the previously reported MNP briarane B-3 was also isolated, with the authors using a combination of VCD, which is the rst reported use of this technique to study this class of NP, and XRD to provide further conrmation of the absolute conguration recently determined using 1 H NMR residual chemical shi anisotropy. 577 Collections of B. stechei (synonymous with B. excavatum) afforded a range of structurally-related diterpenes including briarenols L 1340 (Ie Island), 578 O 1341, P 1342 (aquaculture), 579 U 1343, V 1344 (Ie island), 580 W 1345, X 1346, Y 1347 and Z 1348 (aquaculture) 581 and briastecholides A-C 1349-1351 (Ie Island). 582,583 A large number of known briaranes were also isolated during these studiesof note were the assignment of absolute conguration to briarenol G 1352 and solenolide C 1353 using XRD 578,582 and the reassignment of the structure of solenolide B 1354 to now incorporate a b-oriented 12-acetoxy group.…”
Section: Reviewmentioning
confidence: 99%
“…576 In addition, the previously reported MNP briarane B-3 was also isolated, with the authors using a combination of VCD, which is the rst reported use of this technique to study this class of NP, and XRD to provide further conrmation of the absolute conguration recently determined using 1 H NMR residual chemical shi anisotropy. 577 Collections of B. stechei (synonymous with B. excavatum) afforded a range of structurally-related diterpenes including briarenols L 1340 (Ie Island), 578 O 1341, P 1342 (aquaculture), 579 U 1343, V 1344 (Ie island), 580 W 1345, X 1346, Y 1347 and Z 1348 (aquaculture) 581 and briastecholides A-C 1349-1351 (Ie Island). 582,583 A large number of known briaranes were also isolated during these studiesof note were the assignment of absolute conguration to briarenol G 1352 and solenolide C 1353 using XRD 578,582 and the reassignment of the structure of solenolide B 1354 to now incorporate a b-oriented 12-acetoxy group.…”
Section: Reviewmentioning
confidence: 99%
“…The structure of four previously unreported metabolites, briarenols W-Z ( 156 – 159 ), were established using spectroscopic analyses, while the known ones were identified as solenolide A ( 160 ), briarenolide M ( 161 ), briaexcavatolide F ( 162 ), and brianolide ( 163 ) based on the comparison of their spectroscopic data with literature values. The absolute configuration of 163 was also determined using single-crystal X-ray diffraction analysis [ 64 ]. The methanol extract of the cultured Erythropodium caribaeorum afforded two briaranes, erythrolides A ( 164 ) and B ( 165) , which were also found in the wild type of the same species [ 28 ].…”
Section: Secondary Metabolites Derived From Cultured Soft Coralsmentioning
confidence: 99%
“…In addition, Sarcophyton tenuispiculatum contained 156 which possessed anti-inflammatory activity through inhibiting the production of IL-1β to 56 ± 1% in LPS-stimulated murine macrophage J774A.1 cell at a concentration of 30 µm [ 46 ]. New briaranes 357 and 360 exhibited anti-inflammatory activity by enhancing the release of iNOS (142.03 and 134.11%, respectively) and COX-2 (159.21 and 196.03%, respectively) in LPS-stimulated RAW 264.7 macrophage cells at concentration of 10 µM [ 93 ]. Sarcophyton roseum collected from Egypt contained 158 which possessed anti-inflammatory activity via iNOS inhibition with IC 50 of 50 µM.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…briarenols W-Z 356–359 were the new reported compound and solenolide A 360 was the only known compound being isolated. Compound 357 and 360 were the only compound which exhibited anti-inflammatory activity by enhancing the release of iNOS and COX-2 [ 93 ].…”
Section: Biological Activitiesmentioning
confidence: 99%